Case Report: Carcinosarcoma of the common bile duct: a rare case report with literature review - Lou, Jia-qi; Hu, Zhi-Wei; Liu, Kun; A, Ru-La; Fang, Hao-Yu (Frontiers in Oncology, 2025)
Carcinosarcoma of the common bile duct is an exceedingly rare and highly aggressive malignancy with uncertain therapeutic outcomes. We present a case of a 70-year-old Asian female presenting with progressive jaundice. Contrast-enhanced computed tomography (CT) identified a tumor in the common bile duct. The patient underwent successful radical pancreaticoduodenectomy, and postoperative histopathological analysis confirmed carcinosarcoma with predominant sarcomatoid differentiation. This report underscores the diagnostic challenges and therapeutic considerations for this rare entity, emphasizing the critical role of pathological confirmation.